2021
DOI: 10.1111/ina.12813
|View full text |Cite
|
Sign up to set email alerts
|

Indoor phthalate exposure and contributions to total intake among pregnant women in the SELMA study

Abstract: Phthalates are widely used in consumer products. Exposure to phthalates can lead to adverse health effects in humans, with early‐life exposure being of particular concern. Phthalate exposure occurs mainly through ingestion, inhalation, and dermal absorption. However, our understanding of the relative importance of different exposure routes is incomplete. This study estimated the intake of five phthalates from the residential indoor environment for 455 Swedish pregnant women in the SELMA study using phthalate m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 77 publications
1
4
0
1
Order By: Relevance
“…Levels were higher in flats compared to houses and in smaller homes compared to larger. We have previously reported higher dust levels of BBzP and DEHP in prenatal dust from SELMA families with PVC bedroom flooring (Preece et al, 2021a(Preece et al, , 2021b and similar results were reported in other studies (Bi et al, 2018;Bornehag et al, 2004;Christia et al, 2019). The common use of PVC flooring in Sweden (Larsson et al, 2010) might also contribute to explain the lower Danish BBzP levels compared to this study.…”
Section: Determinantssupporting
confidence: 88%
See 2 more Smart Citations
“…Levels were higher in flats compared to houses and in smaller homes compared to larger. We have previously reported higher dust levels of BBzP and DEHP in prenatal dust from SELMA families with PVC bedroom flooring (Preece et al, 2021a(Preece et al, , 2021b and similar results were reported in other studies (Bi et al, 2018;Bornehag et al, 2004;Christia et al, 2019). The common use of PVC flooring in Sweden (Larsson et al, 2010) might also contribute to explain the lower Danish BBzP levels compared to this study.…”
Section: Determinantssupporting
confidence: 88%
“…Dust samples were analysed using gas chromatography tandem mass spectrometry (GC-MS/MS) as previously described by Weiss et al (2018) and Preece et al (2021aPreece et al ( , 2021b. More information on the chemical analysis is available in the Supplementary Information.…”
Section: Chemical Analysis Of Dustmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, aerosol samples were collected from above-floor levels (aerosols from air conditioner filters), which is more representative of emissions from interior surfaces, compared with floor dust, which can be directly related to the flooring material. 75 Although the study was able to make some inferences on gender-based related influence on the distribution of EDCs in aerosols especially from staff offices, it was, however, very difficult to secure permission from staff of several of the universities used in this study to collect aerosols from their offices. This is largely due to a certain local superstitious belief that these aerosols could be used to hurt them remotely.…”
Section: Strengths and Limitations Of Studymentioning
confidence: 95%
“…실내 바닥에 polyvinyl chloride (PVC)를 사 용한 경우나 6개월 이내 리모델링한 경우, 건축연도가 오래된 경우 소변 중 프탈레이트 대사체 또는 실내 먼지 중 프탈레이트 의 농도가 증가하는 것으로 나타났다. [12][13][14][15][16][17][18] 그러나 나무, 리놀륨 등 다양한 마감재를 사용하는 국외 주택과 다르게, 15,16)…”
Section: 서 론unclassified